Longitudinal study of vitamin D metabolites after long bone fracture. (21st May 2013) - Briggs, Adam DM; Kuan, Valerie; Greiller, Claire L; MacLaughlin, Beverley D; Ramachandran, Manoj; Harris, Timothy; Timms, Peter M; Venton, Timothy R; Vieth, Reinhold; Norman, Anthony W; Griffiths, Christopher J; Martineau, Adrian R
ABSTRACT Animal models suggest a key role for dihydroxylated vitamin D metabolites in fracture healing, as evidenced by increases in serum concentration of 24R, 25‐dihydroxyvitamin D (24R, 25[OH]2D) after long bone fracture. Human studies investigating the kinetics of serum concentrations of 24R, 25[OH]2D, 1, 25‐dihydroxyvitamin D (1, 25[OH]2D) and their parent metabolite 25‐hydroxyvitamin D (25[OH]D) are lacking. We, therefore, conducted a longitudinal study to determine whether total, free, or bioavailable concentrations of these vitamin D metabolites fluctuate in humans after long bone fracture. Twenty‐eight patients with cross‐shaft (diaphyseal) long bone fracture presenting to an emergency department in London, UK, were studied. Serum concentrations of 25(OH)D, 24R, 25(OH)2D, 1, 25(OH)2D, vitamin D binding protein, albumin, and calcium were determined within 48 hours of fracture and again at 1 and 6 weeks postfracture. Concentrations of free and bioavailable vitamin D metabolites were calculated using standard equations. No changes in mean serum concentrations of 25(OH)D or 24R, 25(OH)2D were seen at either follow‐up time point versus baseline. In contrast, mean serum 1, 25(OH)2D concentration declined by 21% over the course of the study, from 68.5 pmol/L at baseline to 54.1 pmol/L at 6 weeks (p < 0.05). This decline was associated with an increase in mean serum corrected calcium concentration, from 2.32 mmol/L at baseline to 2.40 mmol/L at 1 week (p < 0.001) that was maintained at 6 weeks. No changes in free or bioavailable concentrations of any vitamin D metabolite investigated were seen over the course of the study. We conclude that serum 1, 25(OH)2D concentration declines after long bone fracture in humans but that the serum 24R, 25(OH)2D concentration does not fluctuate. The latter finding contrasts with those of animal models reporting increases in serum 24R, 25(OH)2D concentration after long bone fracture.